PID Controller Design for an Industrial Hydraulic Actuator with Servo System - Md Rozali, Sahazati; Rahmat, Mohd Fua'ad; Abdul Wahab, Norhaliza; Ghazali, Rozaimi; Has, Zulfatman (IEEE, 2010)
Electro-hydraulic system (EHS) consists of several dynamic parts which are widely used in motion control application. These dynamic parts need to be controlled to determine direction of the motion. Mathematical model of EHS is required in order to design a controller for the system. In this paper, system identification technique is used for system modeling. Model of the system is estimated by using System Identification Toolbox in Matlab. This process began with collection of input and output data from experimental works. The data collected is used for model estimation. Auto Regressive with eXogeneous input (ARX) model is chosen as model structure of the system. Based on the input and output data of the system, best fit criterion and correlation analysis of the residual is analyze to determine the adequate model for representing the EHS system. By using Ziegler-Nichols tuning method, PID controller is designed for the model chosen through simulation in Simulink. In order to verify this controller, it is applied to the real time system and the performance of the system is monitored. The result obtained shows that the output of the system with controller in simulation mode and experimental works is almost similar. The output of the system also tracked the input given successfully.